The effect of high dose morphine compared to fentanyl infusion on serum levels of mast cell tryptase during cardiac surgery - Barbieri, Mia (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.